The Relationship Between Prenatal Yoga and Sleep Quality Among Third-Trimester Pregnant Women at Juliana Dalimunthe Clinic, Percut Sei Tuan District, Deli Serdang Regency, 2025 - Ester Pakpahan (Journal of Innovative and Creativity, 2025)
The study purpose was to determine the relationship between prenatal yoga and sleep quality among third-trimester pregnant women at Juliana Dalimunthe Clinic, Percut Sei Tuan District, Deli Serdang Regency, in 2025. Sleep disturbance is a common problem in the third trimester, often caused by hormonal changes, physical discomfort, and anxiety before childbirth. Prenatal yoga is a non-pharmacological intervention that combines physical movement, breathing control, and relaxation techniques to improve both physical and psychological well-being during pregnancy. This study was designed to assess whether prenatal yoga routines can enhance the sleep quality of expectant mothers. Materials and methods. This study used a quantitative analytic method with a cross-sectional design. The population consisted of all third-trimester pregnant women visiting Juliana Dalimunthe Clinic in 2025. A total of 30 respondents were selected using total sampling. Data were collected using a structured questionnaire assessing yoga frequency and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the Chi-Square test at a significance level of α = 0.05. Results.The study showed that 76.7% of respondents routinely performed prenatal yoga (>2 times per week), and 56.7% reported good sleep quality. The Chi-Square analysis obtained a p-value of 0.019 < 0.05, indicating a significant relationship between prenatal yoga and sleep quality. Respondents who routinely practiced yoga experienced fewer sleep disturbances and better overall rest compared to those who did not practice regularly. Conclusions.There is a significant relationship between prenatal yoga and sleep quality among third-trimester pregnant women. Routine yoga practice effectively improves relaxation, reduces stress, and enhances both physical comfort and psychological stability during pregnancy. Integrating prenatal yoga into antenatal care programs is recommended to promote maternal health and sleep quality.